Early observations on the use of termite nests by bats - Timm, Robert M. (Therya Notes, 2021)
The remarkable discovery of Neotropical round-eared bats (Phyllostomidae, Lophostoma) actively hollowing out cavities in termite nests for roosting sites has enabled researchers to explore several aspects of their previously unknown behavior. We now know that round-eared bats excavate cavities in Nasutitermes nests that are actively used by the termites and the bats roost only in these cavities, as well as a number of other aspects of the bats’ behavior. In the early 1800s, a British naturalist, Charles Waterton, observed and published that bats “clear out” and roost in termite nests, and how he was able to ascertain if a termite nest was being used by bats. Waterton’s descriptions of this behavior have long been overlooked and now provide us with additional insights on the distribution and ecology of these poorly known bats.